2013
DOI: 10.21059/buletinpeternak.v36i3.1629
|View full text |Cite
|
Sign up to set email alerts
|

Pre Weaning Growth of Bali Calves at Balai Pembibitan Ternak Unggul Sapi Bali

Abstract: <p>Balai Pembibitan Ternak Unggul is a breeding center established by the Government of Indonesia (GOI) to perform preservation, breeding, breeding stock production and development, and also the distribution of breeding stock of Excellent Bali cattle at national level. In the production of excellent breeding stock through the performance test and progeny test. Pre-weaning growth is one of the important indicators for the population growth. The study was aimed to identify the pre-weaning calf growth rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
1
0
Order By: Relevance
“…Furthermore, the straws that used for AI were produced from selected bulls by BIBD Banyumulek. Tavares et al (2012) reported that the BW of Bali calves in the breeding station at Bali island (BPTU-HPT Denpasar) were 18.37±1.65 kg (males) and 18.27±120 kg (females). Kaswati et al (2013) reported that the corrected BW of Bali cattle in the BPTU-HPT Denpasar was 17.80±1.08 kg.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the straws that used for AI were produced from selected bulls by BIBD Banyumulek. Tavares et al (2012) reported that the BW of Bali calves in the breeding station at Bali island (BPTU-HPT Denpasar) were 18.37±1.65 kg (males) and 18.27±120 kg (females). Kaswati et al (2013) reported that the corrected BW of Bali cattle in the BPTU-HPT Denpasar was 17.80±1.08 kg.…”
Section: Discussionmentioning
confidence: 99%
“…The weaning weight of Bali cattle is almost the same as the weaning weight of Bali cattle at the age of 205 days, which are also raised semi-intensively in Makassar, namely 62.6-66.7 kg (Hafsah et al, 2013). Bali cattle calves developed at BPTU Bali cattle can produce a weight at the age of 205 of 87-93 kg (Tavares et al, 2013). Other results showed that Bali calves could reach more than 100 kg when they were five months old.…”
Section: Calf Pre-weaning Body Weightmentioning
confidence: 97%